2009
DOI: 10.1510/icvts.2009.212837
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative administration of landiolol hydrochloride for patients with supraventricular arrhythmia: the efficacy of sustained intravenous infusion at a low dose☆

Abstract: The purpose of this study was to investigate the efficacy of landiolol hydrochloride, a short-acting  1 blocker, by initiating its administration at a low dose (5 g  kg -1  min -1 ) in patients with postoperative supraventricular arrhythmia. The efficacy of landiolol was evaluated in 38 patients who, after developing postoperative atrial flutter or fibrillation, with sinus tachycardia and 2 patients who had a history of paroxysmal atrial fibrillation with frequent atrial extrasystole. The heart rate and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The clinical effi cacy and safety of lowdose landiolol for postoperative tachycardia have been recognized. 12,20 Wariishi et al 20 reported, in a single-arm study, that low-dose landiolol (maximum dosage 7.5 ± 7.6 μg/kg/min) signifi cantly reduced the heart rate and elevated the systolic blood pressure in patients with postoperative supraventricular arrhythmia. In this study, low-dose landiolol (mean maximum dosage 6.6 ± 2.4 μg/ kg/min) demonstrated suffi cient effi cacy for the treatment of postoperative AF following pulmonary resection without side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effi cacy and safety of lowdose landiolol for postoperative tachycardia have been recognized. 12,20 Wariishi et al 20 reported, in a single-arm study, that low-dose landiolol (maximum dosage 7.5 ± 7.6 μg/kg/min) signifi cantly reduced the heart rate and elevated the systolic blood pressure in patients with postoperative supraventricular arrhythmia. In this study, low-dose landiolol (mean maximum dosage 6.6 ± 2.4 μg/ kg/min) demonstrated suffi cient effi cacy for the treatment of postoperative AF following pulmonary resection without side effects.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 This was confirmed by another study using similar to slightly higher doses (7.5 ± 7.6 mcg/kg/min) which showed 89% of patients controlled with minimally impact on blood pressure. 19 …”
Section: Landiolol For Treatment Of Post-operative Atrial Fibrillatiomentioning
confidence: 99%
“…Landiolol shows outstanding cardioselectivity (β1/β2 = 255) with very little α‐blocking action and has an extremely short duration of action (half‐life of 4 min) 6 . Because of its high selectivity for β1‐receptors, landiolol can be administered to patients with respiratory disease 12 . Its dose adjustability allows landiolol to be effective for the treatment of post‐operative AF in patients undergoing cardiovascular surgery, 12,13 and administration of landiolol after cardiovascular surgery does not influence cardiac function parameters such as blood pressure or the cardiac index 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The major pharmacological actions of b-blockers include suppression of abnormal myocardial responses to stimuli and reduction in the heart rate, but a direct defibrillating effect is rare. 12 The cardiovascular effects of landiolol have been compared with those of esmolol in a canine model, showing a similar or slightly more potent b-blocking action of landiolol with significantly less suppression of cardiovascular parameters. 14,15 However, differences of clinical efficacy for SVT between landiolol and other agents have not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation